Verbal list learning and memory profiles in HIV-infected adults, Alzheimer's disease, and Parkinson's disease: An evaluation of the "cortical hypothesis" of NeuroAIDS. Issue 5 (3rd September 2017) - Ciccarelli, Nicoletta; Limiti, Silio; Fabbiani, Massimiliano; Baldonero, Eleonora; Milanini, Benedetta; Lamonica, Silvia; Cauda, Roberto; Di Giambenedetto, Simona; Silveri, Maria Caterina
ABSTRACT: HIV+ population is getting older because of progress in treatments. Yet, there are concerns that Older HIV+ individuals (OHIV+) may be more vulnerable for developing a "cortical" dementia such as Alzheimer Disease (AD). Our aim was to explore the hypothesis that the cognitive deficit extends to ''cortical'' functions in OHIV+ by comparing serial position effects (SPE) in different groups of participants affected by "cortical" or "subcortical" damage. We enrolled a total of 122 subjects: 22 OHIV+ (≥60 years of age), 31 Younger HIV+ (YHIV+) (<60 years of age), 18 participants with AD, 23 subjects with Parkinson Disease (PD), and 28 healthy subjects. All subjects performed verbal learning tasks (VLT) to explore SPE. Factorial analysis of covariance showed a significant effect of "group" ( p  < 0.001) and "task" (Primacy vs Recency) ( p  < 0.001), but no significant group*task ( p  = 0.257) interaction. Compared with healthy subjects ( p  = 0.003), AD had the most severe reduction of Primacy, confirming a primary "encoding deficit, " while PD confirmed a "frontal pattern." OHIV+ showed a memory profile similar to that of PD with a worsening of the cognitive performance in comparison with YHIV+. In conclusion, we did not confirm the "cortical" hypothesis in OHIV+, at least in terms of learning and memory functions.